P5.037 Experience of Rapid HIV Testing Increases Its Acceptability to Clinical Staff in Public Sexual Health Clinics in Sydney. (13th July 2013) - Conway, D P; Guy, R; McNulty, A; Couldwell, D L; Davies, S C; Smith, D E; Keen, P; Cunningham, P; Holt, M
Abstract : Background: Rapid HIV testing is well established in many countries, yet few studies have evaluated the acceptability of rapid testing among clinical staff over time. We assessed staff acceptability of rapid HIV testing before and after its implementation in Australian sexual health clinics. Methods: From September 2011 onwards, men who have sex with men (MSM) attending four Sydney sexual health clinics were offered rapid HIV testing using the Alere Determine HIV Combo assay. Staff were trained in rapid HIV testing using this assay, with staff acceptability assessed via two anonymous questionnaires completed after training and at least six months later. Five-point Likert scales were used, with '1' indicating strong agreement and '5' strong disagreement to a range of acceptability statements. T-tests were used to assess differences in mean Likert scores between rounds, with stratification by staff profession and testing experience. Results: Of 68 trained staff, 67 completed the first questionnaire and 53 the second. Mean scores improved for confidence in conducting rapid testing (1.87 vs 1.44; p < 0.01), confidence in delivery of negative results (1.52 vs 1.25; p < 0.01) and in disagreement that rapid testing was disruptive (3.27 vs 3.83; p < 0.01). Comfort with your own role in rapid testing increased between rounds, particularly for nurses (1.71 vs 1.41; p = 0.04). In round two, doctors had a stronger preference for faster rapid tests than nurses (1.75 vs 2.50; p = 0.02) and stronger agreement that rapid testing interferes with consultations (2.63 vs 3.39; p = 0.01). Belief that patients were satisfied with rapid testing was stronger in staff who had performed > 10 tests than ≤ 10 tests (1.58 vs 2.07; p < 0.01). Acceptability did not vary with experience of false results. Conclusions: Acceptability to staff of rapid HIV testing for MSM increased with time and experience of rapid testing. Differences between professions may indicate variations in staff training and support needs and capacity to adapt to change.